The development of incorpoRATE: A measure of physicians' willingness to incorporate shared decision making into practice. Issue 9 (September 2021) - Berkowitz, Julia; Martinez-Camblor, Pablo; Stevens, Gabrielle; Elwyn, Glyn
Highlights: We developed a measure of physicians' willingness to incorporate SDM into practice. incorpo RATE consists of seven items and is broadly applicable. incorpo RATE addresses domains of SDM use that may present as barriers in practice. Many physicians in our pilot sample had positive views on the general use of SDM. There was less comfort when patient choices differed from physician recommendation. Abstract: Objectives: To develop 'incorpo RATE', a brief and broadly applicable measure of physicians' willingness to incorporate shared decision making (SDM) into practice. Methods: incorpo RATE was developed across three phases: 1) A review of relevant literature to inform candidate domain and item development, 2) Cognitive interviews with US physicians to iteratively refine the measure, and 3) Pilot testing of the measure across a larger sample of US physicians to explore item and measure performance. Results: The final measure consists of seven items that assess physician perspectives on various components of SDM use that may present as barriers in practice. During pilot testing, the majority of physicians expressed positive opinions about the overall concept of SDM, yet were less comfortable acting on informed patient choices when there was known incongruence with their own recommendations. Conclusions: incorpo RATE is a novel physician-reported measure that assesses physicians' willingness to incorporate SDM in practice. Practice implications: incorpo RATE has the potential to help us further understand the limited adoption of SDM and areas of focus for improving the use of SDM in the future. We recommend that incorpo RATE be subject to further psychometric, real-world testing, in order to explore its performance across different samples of physicians and organizations.